The Use of ICT for English Language Learning: A Mixed-Method Study of EFL University Students - Al Arif, Tubagus Zam Zam; Armiwati, Armiwati; Handayani, Reli (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
The current study aims is to investigate the perceptions and expectations of English as a foreign language (EFL) university students regarding the usage of information and communication technology (ICT) in English language learning. This study also investigates the frequency of ICT use among EFL university students for both general and English learning purposes. A convergent parallel mixed methods design was used in this study. Two instruments were used to collect data they are, an online questionnaire and semi-structured interview. A total of 337 students participated in the online questionnaire. A Semi-structured interview was used to gather in-depth information to follow up on the questionnaire to 10 participants purposefully selected who answered the questionnaire with a set of criteria; participants agree to be interviewed; the participants’ mean score of survey result is >3. Quantitative data were analyzed descriptively, and the qualitative data were analyzed and coded thematically. The findings indicated that students spend more time using ICT for general objectives (e.g. social media and entertainment) than for English study. They did, however, demonstrate favorable attitudes regarding the utilization of ICT for English language learning. Furthermore, they intended the campus to provide adequate technological facilities and internet access in each classroom to assist the learning process. Students believe that ICT can assist them enhance their English language skills. As a result, teachers should incorporate more ICT into their English language instruction.